Analisis Perubahan Lahan Terbuka Tambang Pasir Golongan C di Nagari Aia Dingin, Kecamatan Lembah Gumanti, Kabupaten Solok - Devindo Yudilar Fahmi; Dwi Marsiska Driptufany; Defwaldi Defwaldi; Dwi Arini; Fajrin Fajrin (Pusat riset dan Inovasi Nasional, 2025)
Class C sand mining activities in Nagari Aia Dingin, Lembah Gumanti District, Solok Regency have been ongoing since 1999 and continue to expand to this day. This mining provides economic contributions to the local community, but on the other hand, it also has a significant impact on the environment, particularly on land cover changes. This study aims to analyze changes in open land caused by sand mining activities, using remote sensing technology as a monitoring tool. The approach used is descriptive quantitative, through the interpretation of Google Earth satellite imagery in 2015 and 2018 and Sentinel-2 imagery in 2024. Spatial analysis was conducted with the help of ArcGIS software to obtain a visual and numerical picture of land cover changes. The results of the study indicate a significant increase in the area of sand mining from 2015 to 2024. In 2015, the mining area was recorded at 8.72 hectares, and increased to 22.14 hectares in 2024. This indicates an increase in mining land area of 13.42 hectares over a nine-year period. Land use conversion has occurred on a massive scale, from dryland forest, scrubland, and dryland areas to open-pit mining areas. This land cover change has the potential to cause environmental degradation such as erosion, reduced biodiversity, and disruption to regional water systems. These findings underscore the importance of stricter monitoring and sustainable spatial planning in natural resource management. The use of remote sensing technology has proven effective in monitoring the dynamics of land use change and can serve as a basis for formulating environmental policies that are more responsive to the impacts of mining activities.